SENTIMENTALITY VERSUS TRANSFORMATION OF THE HISTORICAL TRADITIONAL RURAL LANDSCAPE (A CASE STUDY: THE LANDSCAPE OF DUTCH LAW SETTLEMENT IN POLAND) - Markuszewska, Iwona (Quaestiones Geographicae, 2019)
The study concentrated on social attitudes towards landscape heritage and the how the place of living was perceived in the context of the transformation of the rural landscape that is currently taking place. The following question was formulated: Are individuals’ approaches to landscape and their attachment to their place of living essential in terms of landscaping and future landscape changes? The research revealed that individual perceptions of rurality and the historical traditional rural landscape (HTRL) varied in different groups of interviewees. Nevertheless, observing the loss of the landscape’s beauty was a traumatic experience, and destructive changes to the landscape were difficult to accept for most of individuals who had spent their lives in the countryside and who felt a strong sense of patrimony. Conversely, the HTRL presented a less important value to other respondents, thus the destruction they observed of the local heritage induced less painful feelings in them. Overall, the results suggest that it is one’s personal interest that will ultimately decide about his/her preservation of the HTRL in the nearest future.